Developing tools of short-term reliability evaluation using a fast sorting technique (FST) / Mohd Khairul Na'im Uyup - Uyup, Mohd Khairul Na'im (2009)
This paper discusses the application of Fast Sorting Technique (FST) that have been developed by Institution of Engineering and Technology and this technique will be applied in the calculation of short terms reliability [1]. By considering speed and accuracy requirements, this technique will quickly select the required number of systems state in descending order probability. After several calculations, the stopping rule for the evaluation will be met. This stopping rule is defined as the relative accuracy of a given reliability index. By using this technique to evaluate the reliability, only a small number of system states are needed to achieve the high accuracy ofthe short-terms reliability and this will take a minimum evaluation of comparisons and also the number of comparisons.